Analysis of the Feasibility Results of Material and Media Aspects of Educational Psychology Textbook - Ernata, Yusvidha (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
This study aims to determine the results of the feasibility of the material and media aspects of the Educational Psychology textbook. This study is a research on the development of an Educational Psychology textbook. The development of this Educational Psychology textbook refers to the 4D model developed by Thiagarajan, et al. (1974) which consists of 4 stages, namely Define, Design, Development, and Disseminate, modified to suit this study. This textbook was tested for feasibility by material and media experts. The instrument used was an expert validation instrument. Based on the results of the study, it can be concluded that the Educational Psychology textbook is declared fit for use as an Educational Psychology textbook by material and media experts.